KNOWLEDGE, ATTITUDE, AND PRACTICE TOWARD PREVENTION AND MANAGEMENT OF MEDICATION ERRORS AMONG PATIENTS: A CROSS-SECTIONAL STUDY - Dewi Latifatul Ilma; Bayu Nugraheni; Nia Kurnia Sholihat; Nialiana Endah Endriastuti (The Indonesian Journal of Public Health, 2026)
Introduction: Medication errors are events that can compromise patients’ safety. A total of 19,639 cases were reported in community pharmacies in Toronto between 2018-2021, with pharmacists and patients identifying 7,053 (35.9%) and 6,533 cases (33.3%), respectively. Several studies have shown that improving patient engagement is a key strategy to reduce the frequency and impact of the errors. Aims: This study aims to assess the knowledge, attitude, and practice (KAP) regarding the prevention and management of medication errors among patients. Methods: A cross-sectional study was conducted using self-administered questionnaires distributed to patients at pharmacies in Banyumas Regency, Central Java, Indonesia. Data were then analyzed quantitatively using descriptive and inferential statistics. The Mann-Whitney U test, Kruskal-Wallis test, and Spearman's rank correlation were applied to identify variables that significantly affected knowledge, attitude, and practice. Results: The results showed that among 385 respondents, the average total knowledge score was 86.18%, which was considered a high level of knowledge. More than 90% of respondents agreed or strongly agreed with statements related to the prevention and management of medication errors, while 37.69% actively engaged in such practice. The results also showed that age, gender, occupation, and education were found to influence patients' attitude and practice. In addition, patients with a positive attitude were more likely to engage in practice that prevents and manages medication errors. Conclusions: The knowledge, attitude, and practice survey confirmed that patients’ attitudes significantly affect their practices in preventing and managing medication errors, indicating the need to strengthen patient practices to reduce medication errors and improve patient safety.